Awareness and Barriers of Industry 4.0 and Education 4.0 between Construction Players and Academicians in Malaysia - Zabidin, Nadia Safura; Belayutham, Sheila; Che Ibrahim, Che Khairil Izam (Journal of Technology Management and Business, 2021)
The digitisation of technologies heavily influences the construction industry with requirements for a new set of knowledge and a skilled workforce. Relatively, the adoption of Industry 4.0 in the work environment changes the current pedagogy at educational institutions through Education 4.0. The importance of adopting and adapting Industry 4.0 with Education 4.0 in construction engineering pedagogy is to create awareness of innovative technologies and to equip graduates with futuristic skills and knowledge. Even though the adoption of Industry 4.0 and Education 4.0 has taken place in the field of construction, limited studies were found on this subject matter, particularly in comparing the awareness between the industry and academia. Hence, this study examines the awareness and barriers of Industry 4.0 and Education 4.0 adoption between the industry players and academicians from the construction engineering perspective. A structured questionnaire survey was developed and distributed within public construction projects and public universities across Peninsular Malaysia. Data for this study were collected through face-to-face meetings and online survey distribution. Findings from the two different categories of respondents with different age range and academic qualifications provide similar, as well as dissimilar outcomes on the awareness and knowledge in accordance with their nature of work. Nonetheless, both distinct respondents have found financial constraint to be the most critical barrier for Industry 4.0 and Education 4.0 adoption. This study provides the revelation on the current state of awareness, knowledge and barriers among the players (industry and academic) in construction engineering and these insights could be further delineated for future action plans in aim to increase the adoption of Industry 4.0 within the field. Keywords: Industry 4.0, Education 4.0, Construction Engineering, Industry Practitioners, Academicians.